The Influence of Leadership and Culture on Performance through the Work Environment - Idris, Muhammad; Hafidulloh, Hafidulloh; Haryati, Endri (UMSurabaya Publishing, 2025)
Transformational leadership has a major influence on improving employee performance, not only in carrying out tasks, but also in terms of providing motivation and inspiration to achieve more optimal work results. Organizational culture also plays a role in shaping behavioral patterns and dynamics of interaction in the work environment. The purpose of this study is to analyze the impact of transformational leadership and organizational culture on employee performance, by considering the role of the work environment as a mediator variables. This study uses a quantitative approach and involves employees of PT. Vermindo Utama Semarang. Data analysis was carried out using the SEMPLS method. The results of the study indicates that transformational leadership directly and indirectly (through the work environment) has a positive and significant influence on performance. The work environment is proven to play an important role as a mediator variables. However, organizational culture does not show a significant influence on the work environment or employee performance, so it cannot be considered as the main factor in improving work performance